(untitled) (Fiep Bulletin - online, 2012)
The purpose of this study was to determine the acute cardiovascular responses to blood pressure (BP), heart rate (HR) and double product (DP) in young, measures taken before, during and after the leg-press exercise performed in different protocols training. The sample consisted of 10 young (16 ± 1 years), body mass (58.9 ± 7.3 kg) and height (1.7 ± 0.1 m), soccer players CR Vasco da Gama-Core Resende without experience in strength training. The data were collected on alternate days. The first day we tested the 10RM load in leg-press exercise. On the second day, there were three sets of 10 repetitions with loads of 50, 75 and 90% of 10RM, Methods of Lorme. On the last day, there were also three sets of 10 repetitions, with loads of 90, 75 and 50% of 10RM, Oxford Method. To measure a frequency FC was used, BP was measured by auscultation. The measurements were performed at rest at the end of heating and of each series and for 20 min (in periods of 5 min post-exercise). ANOVA was used for two entries with repeated measures followed by post-hoc test of Fisher and a significance of p <0.05. There were no differences between the methods for HR (F = 0.16, p = 0.70), SBP (F = 0.24, p = 0.63) and SD (F = 0.0003, p = 0 , 99). However, there was a significant interaction effect between the methods for HR (F = 5.38, p <0.01), SBP (F = 3.75, p <0.02) and SD (F = 5.31 p = 0.02), indicating an increasing trend in all the variables for the method of De Lorme and decreasing to Oxford. We conclude that, according to the data found in this sample, the relationship between exercise with a method of increasing or decreasing load does not change sharply SBP, HR and DP does not result in significant changes in these parameters.